Report of the Study Team on Tribal Development Programmes Maharashtra - Planning Commission (Planning Commission, 1966)
According to the 1961 Census, the population of Scheduled Tribes in Maharashtra is 23.97 lakhs which is 6.06 per cent of the total population of the State and 7.96 per cent of the tribal population in the country. The district-wise distribution of tribal and total population is given in Annexure II.
Committee on Plan Projects, Planning Commission